Attracting Child Psychiatrists to a Televideo Consultation Service: The TeleLink Experience - Tiziana Volpe; Katherine M. Boydell; Antonio Pignatiello (International Journal of Telemedicine and Applications)
Objective. Identify aspects of psychiatry work that are rewarding, as well as those that are challenging, from the perspective of psychiatrists and residents participating in televideo consultation services. Method. A web-based survey was distributed to psychiatrists within the Division of Child Psychiatry at the University of Toronto. Also, semistructured interviews were conducted with six child psychiatrists providing services to a telepsychiatry program. Finally, a focus group interview was held with four psychiatry residents. Results. Child psychiatrists are very comfortable conducting assessments via televideo. Factors identified as being important in the decision to participate in telepsychiatry include assisting underserved communities, supportive administrative staff, enhanced rural provider capacity, financial incentives, and convenience. The study’s qualitative phase identified four themes in the decision to participate in telepsychiatry: (1) organizational, (2) shared values, (3) innovation, and (4) the consultation model. Conclusion. The success of televideo consultation programs in attracting child psychiatrists to provide consultation services to underresourced communities makes an important contribution to psychiatric workforce shortages. Understanding what aspects of telepsychiatry are most appreciated by consulting psychiatrists and residents offers useful strategies to telepsychiatry administrators and medical school educators seeking to attract, train, and retain psychiatry practitioners.